Study of the Rich Afterimage Illusions as an Instrument for Learning of Inflow On-screen Mechanisms for Visual Orientation in Space - Gary M. Zenkin (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
In the paper It has been shown, that with using a complex 3-D configuration of reference points in the presence of structural rich afterimage (rAI) of the entire visual scene, eye movements lead to transformation of the 3-D visual field, representing a complex rotation and scale transformation of the near extrapersonal space with a center somewhere in the region of a hypothetical "cyclopean eye". Experiments have shown that this also results in the recalculation of the coordinates of the observer’s gaze direction, entirely based on inflow information, independent on the signals of the oculomotor and even proprioceptive efferent systems. Three types of rAI illusions are described under different kinds of eye movements. A model is again (after 1976) expressed that these phenomena reflect the work of the "contextually" independent Screen Constancy Mechanisms (SCM), whitch operate at the hypothetical Constant Visual Screen (CVS) level. This level can still be considered as "pseudo-sensory" one of the visual system, located before the formation (appearance) of the object-structured visual field. In experiments, certain conditions affecting the degree of afterimage structural “richness” have been also investigated.